Dynamic stiffness of deep foundations with inclined piles. - Padrón, L. A. (Earthquake engineering & structural dynamics.)
The influence of inclined piles on the dynamic response of deep foundations and superstructures is still not well understood and needs further research. For this reason, impedance functions of deep foundations with inclined piles, obtained numerically from a boundary element?finite element coupling model, are provided in this paper. More precisely, vertical, horizontal, rocking and horizontal?rocking crossed dynamic stiffness and damping functions of single inclined piles and 2 × 2 and 3 × 3 pile groups with battered elements are presented in a set of plots. The soil is assumed to be a homogeneous viscoelastic isotropic half-space and the piles are modeled as elastic compressible Euler?Bernoulli beams. The results for different pile group configurations, pile?soil stiffness ratios and rake angles are presented.